Recursos digitales en el aprendizaje basado en problemas en estudiantes de educación general básica, Unidad Educativa Eugenio Espejo - Martinez Diaz, Diego Armando (2023)
The presentation called “digital resources in problem-based learning in basic general education students, Eugenio Espejo Educational Unit” was made with the objective of determining the influence of digital resources in problem-based learning in Basic General Education students, Eugenio Espejo Educational Unit, therefore, the methodology that refers to the use of the applied, descriptive and exploratory type was demonstrated; the mixed research approach, the inductive and analytical methods that are applied through the survey technique through the respective questionnaires carried out to the students and teachers of the eighth, ninth and tenth levels, using digital channels such as Google Forms, which resulted in the fact that digital resources are not frequently used for the development of activities, consequently, there is a waste of the advantages that technology provides, this is associated with the lack of resources and adequate spaces within the institution based on student demand. However, the bibliographic data obtained and the information provided by educational control entities at the national and international level support the premise that the EGB students of the Eugenio Espejo Educational Unit, who use digital resources in problem-based learning . They will achieve adequate development of competencies and skills.